2021
DOI: 10.1016/j.ebiom.2021.103474
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism in childhood neurodevelopmental disorders

Abstract: Whereas energy function in the aging brain and their related neurodegenerative diseases has been explored in some detail, there is limited knowledge about molecular mechanisms and brain networks of energy metabolism during infancy and childhood. In this review we describe current insights on physiological brain energetics at prenatal and neonatal stages, and in childhood. We then describe the main groups of inborn errors of energy metabolism affecting the brain. Of note, scarce basic neuroscience research in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 121 publications
3
17
0
Order By: Relevance
“…Depression is often accompanied by disrupted energy metabolism 53–55 . In the present study, metabolism alterations were identified in all three brain regions of CUMS rats.…”
Section: Discussionsupporting
confidence: 47%
“…Depression is often accompanied by disrupted energy metabolism 53–55 . In the present study, metabolism alterations were identified in all three brain regions of CUMS rats.…”
Section: Discussionsupporting
confidence: 47%
“…Interestingly, there are often overlapping symptoms experienced by people diagnosed with various NDDs. These include cognitive and learning disabilities ( Pope and Kern, 2006 ; Gold et al, 2008 ; Cicero et al, 2014 ; Wang et al, 2017 ; Banker et al, 2021 ), decreased social behaviors ( Nijmeijer et al, 2008 ; Hooley, 2010 ; Uekermann et al, 2010 ; Savla et al, 2013 ; Staikova et al, 2013 ; Supekar et al, 2013 ; Perepa, 2014 ; Cotter et al, 2018 ; Porcelli et al, 2019 ), altered sleep patterns or disrupted circadian rhythms ( Williams et al, 2004 ; Cohrs, 2008 ; Konofal et al, 2010 ; Stein et al, 2012 ; Hvolby, 2014 ; Myles et al, 2016 ; Kaskie et al, 2017 ; Shelton and Malow, 2021 ), as well as metabolic or gastrointestinal disturbances ( Richardson and Ross, 2000 ; Singh et al, 2020 ; Oyarzábal et al, 2021 ). It is important to note that symptoms shared across different NDDs can manifest differently based on the specific disorder and the individual person.…”
Section: What Are Neurodevelopmental Disorders?mentioning
confidence: 99%
“…7 ). Intrauterine growth restriction and neurodevelopmental disorders such as epilepsy, schizophrenia and autism comprise alterations in the metabolism of glucose and mitochondrial oxidation ( Devaskar and Chu, 2016 ; Jones et al, 2020 ; Vannucci and Vannucci, 2000 ; Jha et al, 2016 ; A et al, 2021 ) with impairment in neuronal communication but not significant cell death. These alterations may well correlate with some processes observed in infected late hi-NPCs, thus, potentially explaining the abnormalities observed in newborns when ZIKV infection occurs at later stages during pregnancy.…”
Section: Discussionmentioning
confidence: 99%